Poly(4-methyl-1-pentene)/MWNT nanocomposites - Patil, Prashant A.; Wanjale, Santosh D.; Jog, Jyoti Prakash (E-Polymers, 2008)
Nanocomposites of poly(4-methyl-1-pentene) (PMP) with various weight fractions of multiwall carbon nanotubes (MWNT's) were prepared by melt compounding. The nanocomposites are characterized for structure using scanning electron microscopy. The viscoelastic behavior of the nanocomposites is investigated in solid as well as melt state. The study reveals a significant increase in storage modulus especially in the rubbery regime of the polymer matrix and reduced tan delta. Rheological properties in melt show that the complex viscosity and shear storage modulus are increased as a result of incorporation of MWNT. A systematic decrease in the cross over frequency is noted which is attributed to the increased relaxation time. In dielectric analysis, composition dependent enhanced permittivity and conductivity are observed. The thermal stability of the polymer is found to be significantly improved in presence of MWNT's.

Characterisation of copolymer, poly (hydroxybutyrate-co-hydroxyvalerate) (PHB-co-PHV) produced by halomonas campisalis (MCM B-1027), its biodegradability and potential application - Kulkarni, Snehal O.; Kanekar, Pradnya P.; Jog, Jyoti Prakash; Patil, Prashant A.; Nilegaonkar, Smita S.; Sarnaik, Seema S.; Kshirsagar, Pranav R. (Bioresource Technology, 2011)
Characterisation of polyhydroxyalkanoate (PHA) film produced by haloalkalitolerant Halomonas campisalis (MCM B-1027) in 14 L SS fermenter revealed it to have composition of monomer units, HB:HV as 96:4 as analysed by (1)H NMR indicating the PHA as a co-polymer of PHB-co-PHV, molecular weight by gel permeation chromatography as 2.08 x 10(6), melting temperature 166.51 degrees C, tensile strength 18.8 MPa; two relaxations namely beta transition corresponding to the glass rubber transition and alpha transition corresponding to crystalline relaxation by Dynamic Mechanical Thermal analysis and only one relaxation corresponding to MWS interfacial polarisation with activation energy of 129 kJ/mol by broadband dielectric spectroscopy. Optical microscopic studies showed typical Maltese-cross pattern of spherulites. The PHA film was found to be biodegradable by standard ASTM method as well as by soil burial method. The leak proof polymer bags prepared from the film could be used as a packaging material. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Biodegradable polymer; Copolymer PHB-co-PHV; Dielectric relaxation spectroscopy; Dynamic mechanical analysis; Halomonas

Bile acid hydrazides: gelation, structural, physical and spectroscopic properties - Pore, Vandana S.; Agalave, Sandip G.; Pharande, Shrikant G.; Patil, Prashant A.; Kotmale, Amol S. (New Journal of Chemistry, 2015)
Synthesis and gelation properties of a series of novel bile acid hydrazides are presented. These compounds are found to undergo self-assembly leading to organogelation in certain organic solvents. Compound 1 was found to be the most ``effective'' gelator in this series. The properties of this gel have been thoroughly investigated by conventional methods typical for molecular gel studies. Sol gel transition temperature (T-g) of chloroform gels of compounds 1 and 3 was found to increase with increase in the chain length. Sol-gel transition was probed using the isothermal time test and results show that there is instantaneous increase in both the moduli after shear melting, which suggests that the kinetics of formation of the network was very fast. IR and NMR studies revealed hydrogen bonding between amidic carbonyl in the side chain and hydroxyl groups of cholic acid.